The Impact of Work Culture and Leadership on Employee Performance at Pegadaian Boulevard Kelapa Gading Branch Through Motivation as an Intervening Variable - Supriyanto, Supriyanto; Chaerudin, Chaerudin (Dinasti International Journal of Digital Business Management, 2023)
In order to finish the mission, human resources are necessary. Only human resources such as emotions, reason, abilities, desires, knowledge, and skills can be replicated. Operational challenges will arise for the organisation in the absence of sufficient human resources. Human resources are one of the crucial elements that must be taken into account in order to attain organisational goals. This is a result of human resources' involvement in and management of the business's operations. A quality human resource base is required to keep up with the rapid advancement of research. Human resources are crucial in many different industries these days. The aim of this research is to ascertain the impact of motivation, work culture, leadership, and performance. Because the author's research approach is based on true, objective, measurable, logical, and methodical data, it is quantitative in nature. All of the employees of the PT Pegadaian Kelapa Gading Boulevard Branch made up the whole population sample used in this investigation, and samples were then taken from each employee. There are thirty-six people in total. This study's analysis approach is variant-based structural equation modelling, and the Partial Least Square (PLS) software tool is used during the data processing step to generate relevant hypotheses and models. The findings demonstrated that at Pegadaian Boulevard Kelapa Gading Branch, leadership had a minimally negative impact on worker performance and a good effect